2017
DOI: 10.1186/s41038-017-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

The progress of Chinese burn medicine from the Third Military Medical University—in memory of its pioneer, Professor Li Ao

Abstract: Professor Li Ao was one of the founders of Chinese burn medicine and one of the most renowned doctors and researchers of burns in China. He established one of the Chinese earliest special departments for burns at Third Military Medical University (TMMU) in 1958. To memorialize Professor Li Ao on his 100th birthday in 2017 and introduce our extensive experience, it is our honor to briefly review the development and achievement of the Chinese burn medicine from TMMU. The epidemiology and outcomes of admitted bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…After further analysis of the etiology, we found that scalding was the priority cause to burns in females, accounting for over 60 percent of the total female patients (Table 1). Surprisingly, in another developing country India, similar nding has been reported before that Indian population of young females between the ages of 16 Considering the priority etiology of scalding, we assumed the rst reason was that women still took the main responsibility of cooking for the family, so they were more likely exposure to hot water/oil and cooking ames compared to men. Secondly, more and more women were involved in the workforce.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…After further analysis of the etiology, we found that scalding was the priority cause to burns in females, accounting for over 60 percent of the total female patients (Table 1). Surprisingly, in another developing country India, similar nding has been reported before that Indian population of young females between the ages of 16 Considering the priority etiology of scalding, we assumed the rst reason was that women still took the main responsibility of cooking for the family, so they were more likely exposure to hot water/oil and cooking ames compared to men. Secondly, more and more women were involved in the workforce.…”
Section: Discussionsupporting
confidence: 58%
“…An estimated of 1,300 burn patients are admitted to the center annually. The year of 2018 was the 60th anniversary of this center; and a lot of achievements on burn treatment have been reached including the Chinese Rule of Nine, uid resuscitation protocol, experience in inhalation injury, wound treatment strategies, prevention and treatment of burn infections [16].…”
Section: Study Settingmentioning
confidence: 99%
“…After admission, all patients received standard care for burns [ 20 , 21 ], which included the following: First aid Fluid resuscitation, resuscitation with crystalloids followed by colloids according to the Third Military Medical University protocol [ 22 ] (target hourly urine output greater than 0.5 ml/kg/h), as well as haemodynamic monitoring by pulse-indicated continuous cardiac output when necessary Management of inhalation injury Early excision and skin graft, which were performed after fluid resuscitation at 3–7 days post-burn [ 23 ]; the covering includes autologous skin grafts, meshed grafts, MEEK grafts, micro-skin autografts overlaid with large sheet allograft, single large sheet allograft, or heterogenetic porcine skin grafts Glucose control Prevention and treatment of infection by systemic administration of antibiotics Prevention of stress ulcer Early enteral nutrition Organ support therapy Bedside rehabilitation training …”
Section: Methodsmentioning
confidence: 99%
“…An estimated of 1,300 burn patients are admitted to the center annually. The year of 2018 was the 60th anniversary of this center; and a lot of achievements on burn treatment has been reached including the Chinese Rule of Nine, uid resuscitation protocol, experience in inhalation injury, wound treatment strategies, prevention and treatment of burn infections 26 .…”
Section: Study Settingmentioning
confidence: 99%